Delineating phenotypic heterogeneity in human regulatory T cells across developmental stages and therapeutic sources - Santosh Nirmala, Samikshya; Hu, Yueyuan; Floegel, Friederike Dorothea; Cruz, Hugo; Morgenstern, Johanna; Platz, Alexander; Vollroth, Marcel; Fuchs, Anke (Frontiers in Immunology, 2026)
BackgroundFOXP3+ regulatory T cells (Tregs) play a pivotal role in maintaining immune homeostasis and self-tolerance. Despite advances in Treg-based immunosuppressive therapies, precise identification of human Tregs facilitating their isolation with high purity remains challenging because canonical markers such as FOXP3 and CD25 are also induced in activated CD4+ effector T cells (Teffs). This study aims to leverage adult peripheral blood, umbilical cord blood, and pediatric thymic tissue to precisely characterize human Tregs and to gain deeper insights into heterogeneity across sources and developmental stages.MethodsWe conducted extensive flow cytometric analysis of 31 extra- and intracellular markers expressed by human Tregs, followed by an in-depth comparison of Tregs and Teffs, as well as between Tregs derived from all three sources.ResultsOur results showed that, while most markers were shared with Teffs, the transcription factor Helios, the co-inhibitory receptors CTLA-4 and TIGIT, and the glycoprotein receptor GPA33 were expressed by a higher proportion of Tregs than Teffs across sources. Contrary, a consistently higher proportion of Teffs than Tregs expressed the co-stimulatory receptors CD26 and CD226. Thymocytes displayed marked heterogeneity, containing Tregs at distinct developmental stages and recirculating peripheral Tregs. The proportion of CD25+FOXP3lo/– CD4 single positive (SP) precursor cells expressing Treg specific markers Helios, TIGIT and CTLA-4 was significantly lower than of CD25+FOXP3+ double-positive (CD4+CD8+) Tregs and mature CD25+FOXP3+ CD4SP Tregs. These findings challenge the previously held notion that CD25+FOXP3lo/– precursors uniformly mature into CD25+FOXP3+/hi Thy-Tregs. As this subset differs from mature Thy-Tregs primarily by FOXP3 expression - a marker unsuitable for live-cell sorting - conventional isolation methods fail to exclude this immature subset. Importantly, our study identified the surface markers CD45RA/CD45RO, GPA33, TIGIT, and PD-1 to exclusively distinguish mature Thy-Tregs from these precursors. Moreover, our study provides a detailed characterization of highly activated recirculating peripheral Tregs within the thymocytes. Among the three sources examined, cord blood-derived Tregs exhibited the greatest phenotypic uniformity compared with adult blood- and thymus-derived Tregs.ConclusionOverall, this study provides highly detailed insights into the heterogeneity of Tregs across distinct developmental stages and therapeutic sources, while also contributing towards improved isolation strategies for therapeutic approaches.